Analisis Pompa Kalor Siklus Udara Tertutup Untuk Pengeringan Pisang - Joko Harianto; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In principle, the drying process involves the process of heat transfer and mass movement that occurs simultaneously. First, the heat must be transferred from the heating medium to the material. Furthermore, after water evaporation occurs, the moisture formed must be moved through the material structure to the surrounding medium. The purpose of this study is to determine the time required to dry bananas with water content that has been determined. The calculation analysis of consumption and energy cost for banana dryer system using heat pump. It is based on result oftheoritical calculations with closed air circle. The advantages of this study as development in the field of energy saving with refrigeration technology and air conditioning.From the experimental results and the analysis obtained the average temperature of dryer indoor that is 44,5oC and 47oC.Keywords: Drying, Temperature, Banana dryer system